ADDRESSING THE CHALLENGES OF TEACHING ENGLISH GRAMMAR - Jo’rayeva Marjona Shuhratovna; Normuratova Manzura Mamayusuf qizi (Web of Journals Publishing, 2023)
This article explores the multifaceted challenges teachers face in the field of English grammar teaching. It critically examines issues ranging from the diverse needs of students and the complexity of grammar rules to engaging teaching methods. The author explores strategies for adapting instruction to accommodate students with different language and proficiency levels. In addition, the article explores the complexities inherent in English grammar, looking at irregularities, exceptions, and nuanced usage. It discusses innovative and interactive approaches to teaching and emphasizes the importance of technology, games, real-life examples, and collaborative activities in creating a dynamic learning environment. Balancing teaching the form and function of grammar and assessing students' grammar skills is considered. The article also highlights the importance of continuing professional development for teachers and the role of cultural sensitivity in teaching English grammar. By providing insight into these issues, the article aims to provide teachers with valuable guidance on how to overcome barriers and improve the effectiveness of grammar teaching.
Keywords: grammar, principle, training, communication, student, teacher, fluent, method, vocabulary, forms of training